L’attrait des petites villes, une chance pour redynamiser leur centralité ? - Jean-Charles Edouard (Belgeo)
Small towns, considered as poles of urban centrality, are facing a decline of their attractiveness. This explains why the concept of attractiveness has become one of the main topics of their local policies. Until recently, place attractiveness was based mainly on the analysis of attracted objects (such as different kinds of inhabitants or of activities) and on economic indicators. This dominant conception seems incomplete to define public policies as it does not really take into account important issues (quality of life, sustainable development, etc.) that must be considered, especially by small towns’ stakeholders willing to develop residential economy. It is necessary to elaborate a broader qualitative conception of attractiveness, including individual and collective representations for policy purposes.